Dampak Kebijakan Harga Pembelian Pemerintah Terhadap Produksi Gula Kristal Putih - Rachmadhan, Aditya Arief; Kusnadi, Nunung; Adhi, Andriyono Kilat (Politeknik Negeri Lampung, 2021)
The policy objective of government purchase price (harga pembelian pemerintah – HPP) of plantation white sugar in Indonesia is to increase the production. However, while the government increase the HPP, the production was decreased. The purpose of this study was to analize the impact of HPP policy on production of plantation white sugar in Indonesia. This study uses ex-post simulation based on econometrics model (build from monthly time series data from 2012 until 2017, consist of 13 equations and estimated using 2SLS method). The result shows that an increase in HPP causes an increase in plantation white sugar production. However, an increase in labor wages cause decreased in production. The increase HPP also causes an increase in producer surplus. Based on producer surplus, the biggest impact of the increase in HPP was felt by the farmers.